Pesquisa de vírus respiratórios em crianças asmáticas (exacerbadas e não exacerbadas) e em crianças não asmáticas com sintomas de infecção respiratória aguda, em Goiânia-Goiás - Costa, Lusmaia Damaceno Camargo (2014)
Objective: to describe the prevalence of respiratory viruses in children with asthma during exacerbation and compare with those non-exacerbated and nonasthmatic children during acute respiratory infection. Methods: In this cross-sectional study nasopharyngeal aspirate/swab from children (4-14 years) was collected between August-2012 and August-2013 in a city (Goiânia) in Center-Brazil. There were 92 with exacerbated asthma (EA), 72 non-asthmatic with acute respiratory infection (ARI) in emergency room, and 61 non exacerbated asthmatic (NEA) treated in specialized clinics. The samples were tested to indirect immunofluorescence using the Respiratory Panel I (Chemicon. MA, USA) and RT-PCR kit rhinovirus. The study was approved by the ethics committee of the HC / UFG and statistical analysis performed with the SPSS v.20 software (SPSS Inc., Chicago, IL). The chi-square test was used to compare categorical variables and Kruskal-Wallis test to compare medians, pvalue< 0.05 was considered significant. Results: the sample consisted of 225 children, mostly male (59.5%) with median age of seven years. The viral prevalence was 91.1% and rhinovirus was the most commonly detected (67.6%), with no significant difference in incidence among all groups. Other viruses were identified: influenza A (13.2%), adenovirus (7.5%), influenza B (3.5%), respiratory syncytial virus (2.8%), parainfluenza 2 (2.8%) and parainfluenza 1 (2.5%). Adenovirus were more frequent in ARI (p=0.25). The EA group compared to the NEA group had cough at night (p<0.01), symptoms on exertion (p<0.01), medical visits (p<0.01) and hospitalizations for asthma (p<0.01) in the last 12 months and less use of medication (8.6%) for asthma control (p<0.01). Conclusions: the prevalence of viral detection was high (90.1%) in all patients (EA, NEA and ARI) and rhinovirus was the most prevalent agent, without differences between groups while adenovirus was more common in nonasthmatic children. Children with exacerbated asthma had parameters of uncontrolled disease in the last 12 months. Asthmatic children with nonexacerbated disease had no exacerbation although most of them had viruses in their nasopharynx, probable because of the regular use of inhaled corticosteroids.